Body art and performance: the body as language - Vergine, Lea; Vergine, Lea (Skira, 2007)
When The Body as Language ("Body-art" and Performance) appeared in 1974, it was immediately a huge publishing hit, reviewed by some of the most influential art historians and writers (Giulio C. Argan, Edoardo Sanguineti, Max Kozloff, Lucy Lippard, François Pluchart, Peter Gorsen, Evelyn Weiss and many others). A direct testimony of the birth and development of one of the most controversial art trends, Lea Vergine's book avails of a series of texts by the artists themselves, whom the author had asked to contribute with a statement about the illustrations of their work. Featuring a thorough documentation of original photographs and film photograms, videotapes, happenings, actions and performances, the book analyses the evolution of this phenomenon through the works of sixty artists, including Gina Pane, Gilbert & George, Urs Lüthi and Katharina Sieverding, Rebecca Horn, Trisha Brown, Günter Brus and many others who have worked with and on the body. In an absolutely unusual publishing event, nearly thirty years after the first edition, the text--by now a classic--is republished with all the original photographic material. The volume is enhanced and brought up-to-date by an afterword by Lea Vergine, who observes the changes of Body Art throughout the nineties: Orlan, Stelarc, Ron Athey, Franko B., Yasumasa Morimura, Jana Sterbak, Matthew Barney are "virtuosos of disorder and hungry for afflictions of any and every kind, mystics--like persons who display the subjection of their bodies to cruel and invasive devices, or who revel in virtual fantasies of such self-inflicted pains--destroy themselves in order newly to find themselves. . . . They finally pay a visit to the world of the saints and victims, exploring and prolonging its seductions.
Keywords: art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; performance; premier cycle; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques